2011
DOI: 10.1111/j.1399-0012.2010.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of pediatric renal transplantation: a single center experience

Abstract: Renal transplantation is the optimal treatment for pediatric end-stage renal disease. We examined 51 children <20 yr old who underwent a total of 52 living-donor renal transplantations at Osaka University Hospital between 1972 and 2004. The mean age at transplantation was 13.7 (3-19 yr). The mean duration of follow-up was 16.5 yr. The five-, 10-, and 20-yr patient survival rates following renal transplantation were 94%, 90%, and 87%, respectively. The five-, 10-, and 20-yr graft survival rates were 76%, 65%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
(25 reference statements)
4
12
0
Order By: Relevance
“…This compares favourably to published long-term outcome from national and regional registries. The published studies on the outcome of paediatric renal transplants are summarised in Table 4 [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…This compares favourably to published long-term outcome from national and regional registries. The published studies on the outcome of paediatric renal transplants are summarised in Table 4 [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Because of a severe shortage of deceased donors, >80% of the transplanted kidneys come from live family donors in Japan . This led our philosophy to restrict to renal transplants in children weighing ≥15 kg because we believe that it is safer for them to receive a transplant from a living donor.…”
Section: Discussionmentioning
confidence: 99%
“…Many single center studies from different countries have reported the outcome of pediatric living‐donor renal transplantation . However, few single center studies are available on the long‐term outcome at 15–20 yr post‐transplant . In particular, only one single center study of pediatric renal transplantation has been reported from Japan .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CS induce overt elevation of serum IGF-1 levels, which results in the potential development of IGF resistance, one of the main factors responsible for persistent growth retardation45). Bone maturation and linear growth are delayed and arrested by long-term, high-dose CS therapy46), particularly when the dosage exceeds 0.5 mg/kg/day47). Therefore, the initial dose should be low in the range of 0.2 to 0.4 mg/kg (5 to 15 mg/m 2 ) per dose for treatment maintenance.…”
Section: Adverse Effects Of Long-term Drug Therapymentioning
confidence: 99%